Evaluation of the Antifungal Efficacy of Natural Gum Acacia and Aloe Vera against Candida albicans on Conventional and Digital Denture Base Materials: An In Vitro Study - El-Din, Mai Salah; Zeitoun, Hend; Fayad, Mostafa I.; Zafar, Muhammad Sohail; Al-Gabri, Redhwan Saleh; Alqutaibi, Ahmed Yaseen; Moussa, Rania (European Journal of Dentistry, 2025)
This study evaluated the efficacy of Acacia Arabica and aloe vera solutions versus commercial effervescent tablets on Candida viability and adhesion to various denture bases with different materials and manufacturing techniques.A total of 96 square-shaped denture base specimens (24 per group) were fabricated from heat-cured polymethyl methacrylate (PMMA), thermoformed polyamide (FlexiUltra), milled computer-aided design and computer-aided manufacturing (CAD/CAM; Avadent), and 3D-printed (FormLabs) resins. Specimens were allocated into a control group (distilled water) and three experimental groups (n = 6 per group) based on the immersion solutions: Gum acacia (GA), aloe vera, and alkaline peroxide denture cleansers. One specimen from each material subgroup was prepared for qualitative assessment. All specimens were incubated with Candida albicans for 48 hours and immersed in the designated disinfectant solution for 8 hours. Anti-C. albicans biofilm activity was assessed quantitatively using an MTT assay and qualitatively using a confocal laser scanning microscope (CLSM).One-way analysis of variance (ANOVA) was employed for mean comparison, and data were considered significant at p < 0.05.The reduction in mean Candida viability was greatest in the alkaline peroxide tablets across all denture base materials, followed by GA and aloe vera (p < 0.001). GA demonstrated a statistically significant reduction in Candida levels in the thermoplastic polyamide (p < 0.001). The mean viability of Candida in both alkaline peroxide tablets and GA was statistically similar in digital denture bases (p > 0.05).The antifungal efficacy of alkaline peroxide denture cleansers was determined to be the highest. The cost-effective GA may serve as a viable denture disinfectant, particularly for thermoformed polyamide denture bases.
Keywords: gum acacia; aloe vera; CAD/CAM; PMMA; Candida albicans; denture base; denture disinfectant